2020
DOI: 10.1002/aenm.202001440
|View full text |Cite
|
Sign up to set email alerts
|

Lithium Difluorophosphate‐Based Dual‐Salt Low Concentration Electrolytes for Lithium Metal Batteries

Abstract: The safety hazards and low Coulombic efficiency originating from the growth of lithium dendrites and decomposition of the electrolyte restrict the practical application of Li metal batteries (LMBs). Inspired by the low cost of low concentration electrolytes (LCEs) in industrial applications, dual‐salt LCEs employing 0.1 m Li difluorophosphate (LiDFP) and 0.4 m LiBOB/LiFSI/LiTFSI are proposed to construct a robust and conductive interphase on a Li metal anode. Compared with the conventional electrolyte using 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
128
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 71 publications
1
128
0
Order By: Relevance
“…[ 64 , 68 ] Therefore, various salts are probed to obtain the ideal SEI. Recently, dual‐salt or tri‐salt systems, such as, lithium difluorophosphate‐lithium bis(oxalato)borate (LiDFP‐LiBOB), [ 18 ] lithium bis(trifluoromethanesulfonyl)imide‐lithium bis(oxalato)borate (LiTFSI‐LiBOB), [ 69 ] lithium bis(trifluoromethanesulfonyl)imide‐lithium bis(oxalato)borate‐lithium hexafluorophosphate (LiTFSI‐LiBOB‐LiPF 6 ), [ 68 ] become a thriving trend and the synergistic effect among different salts has been verified beneficial to form SEI with favorable components and proper proportion of these components. In a dual salt (LiDFP‐LiBOB) system, the Li//LiFePO 4 battery operated stably for 300 cycles at the current density of 2 mA cm −2 .…”
Section: Strategies To Solve Issues Of the Lithium Anodementioning
confidence: 99%
See 2 more Smart Citations
“…[ 64 , 68 ] Therefore, various salts are probed to obtain the ideal SEI. Recently, dual‐salt or tri‐salt systems, such as, lithium difluorophosphate‐lithium bis(oxalato)borate (LiDFP‐LiBOB), [ 18 ] lithium bis(trifluoromethanesulfonyl)imide‐lithium bis(oxalato)borate (LiTFSI‐LiBOB), [ 69 ] lithium bis(trifluoromethanesulfonyl)imide‐lithium bis(oxalato)borate‐lithium hexafluorophosphate (LiTFSI‐LiBOB‐LiPF 6 ), [ 68 ] become a thriving trend and the synergistic effect among different salts has been verified beneficial to form SEI with favorable components and proper proportion of these components. In a dual salt (LiDFP‐LiBOB) system, the Li//LiFePO 4 battery operated stably for 300 cycles at the current density of 2 mA cm −2 .…”
Section: Strategies To Solve Issues Of the Lithium Anodementioning
confidence: 99%
“…Li 2 BO x , the decomposition products of LiBOB, contributed to suppressing the dissolution of the organic species in SEI and enhanced its flexibility. [ 18 ] Jin et al. [ 68 ] confirmed that lithium symmetric battery was more stable in a tri‐salt system (LiTFSI‐LiBOB‐LiPF 6 ) than in LiPF 6 or dual‐salt (LiTFSI‐LiBOB) systems ( Figure 2 a ), which was due to that tri‐salt system facilitated the formation of high‐quality SEI that contains sufficient both Li 2 CO 3 and ROCO 2 Li.…”
Section: Strategies To Solve Issues Of the Lithium Anodementioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the external pressure is the key factor to realize the excellent electrochemical performance of the anode-free Li-metal batteries.T he electrochemical performance of anode-free Li-metal batteries is the best ever reported. [86] When athin layer of graphite is coated on the Cu current collector to form aL i-ion/Li metal battery, [87] ap rolonged cycle life is achieved.…”
Section: Methodsmentioning
confidence: 99%
“…As stated above, SEI film plays a crucial role in determining the property of LMBs; the stable and compact SEI film can effectively repress the side reaction and dendrite growth. The components and structure of SEI strongly depend on the dissociation degree of salts, different salts concentration electrolytes, [15,16] the stability of different solvents, [17] and the strength of the solvation of electrolytes. [18] Therefore, many additives are used to assist in the formation of stable SEI film on Li metal surface, such as fluoroethylene carbonate (FEC), LiNO 3 , ionic liquid, and Lithium chloride.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%